A retrospective study on the regional benefits and spillover effects of high-speed broadband networks: Evidence from German counties - Wolfgang Briglauer; Niklas S. Dürr; Klaus Gugler (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
There is still hardly any empirical evidence on how divergent broadband technologies, and, by extension, bandwidth levels, influence GDP growth, or on the extent of spatial externalities at a regional level. Our study aims to assess the economic benefits of high-speed broadband networks within and across neighbouring counties in Germany. Utilizing a balanced panel dataset of 401 German counties with data from 2010-2015 as well as different panel estimation techniques, we find that the availability of high-speed broadband (which enables transfer rates of 50 Mbit/sec and higher) has a small but significant positive effect on regional GDP growth in the average German county, when compared to normal broadband availability. Furthermore, we find that broadband deployment in German counties induces substantial economic benefits in terms of direct effects and regional externalities. According to our main estimation results, an increase in bandwidth coverage of 50 Mbit/sec and higher by one percentage point induces arise in regional GDP of 0.05%. This effect is almost doubled if we also take regional externalities into account and is of particular relevance for urban counties. Furthermore, our cost-benefit analysis suggests substantial efficiency gains, as the total economic benefits of subsidy programs to encourage broadband expansion substantially exceeded their associated costs.
Keywords: H23; H54; L96; L98; R11; R58; 330; high-speed broadband infrastructure; economic growth; spatial externalities; German counties; panel data